The comparative study on the absorption and excretion of caffeine in rats orally administered ripened and green Pu-erh tea - Zhang, Liang; Sheng, Jun; Long, Piaopiao; Meng, Qilu; Wan, Xiaochun; Zhang, Zhengzhu (Progress in Nutrition, 2019)
Purpose: Ripened pu-erh tea is one of the most famous Chinese dark teas in Eastern Asian and Western China. When rats were orally administered ripened pu-erh aqueous extract (caffeine dose 135 mg/kg), the maximum plasma concentration (Cmax) of caffeine was 53.96±9.46 µg/mL, which was significantly less than those of green pu-erh tea (90.95±20.93 µg/mL). Furthermore, area under the plasma concentration–time curve (AUC0-t) of caffeine of ripened pu-erh tea was also significantly decreased. The total fecal content of caffeine of rats given ripened pu-erh tea was 4.83 mg, which was almost two-folds of the fecal caffeine of rats given green pu-erh tea (2.46 mg). The in vitro human intestinal epithelial cell linetransportation results also showed that the caffeine of ripened pu-erh tea was less transported from apical (AP) to the basolateral (BL) side. These results indicated post-fermented pu-erh tea impeded the absorption of caffeine but promoted its excretion.